Tort Law and Judicial Risk Regulation: Bipolar and Multipolar Risk Reasoning in Light of Tort Law's Regulatory Effects. (22nd March 2018) - DE JONG, Elbert R
Abstract: Although judicial decisions in tort law primarily determine the (correlative) responsibilities and liabilities of the proceeding parties, they also have regulatory effects on non-litigants. In this contribution, these regulatory consequences of tort law will be analysed in light of a court's quest when it decides a tort claim involving (uncertain) risks. It will be argued that decisions in tort law about uncertain risks involve the possible occurrence of a false positive (eg accepting liability for a non-existing risk) and a false negative (eg denying liability for a real risk). False positives and false negatives have adverse consequences for the parties to the proceedings but, bearing in mind the regulatory effects of tort adjudication, potentially also for non-litigants. While courts might want to avoid both, scientific uncertainties and complexities make it difficult for them to assess to what extent there is a chance of either a false positive or a false negative occurring. Therefore, they necessarily need to determine which party bears the risk of the involved errors. In addition, the question arises whether courts should also take the potential regulatory consequences of their rulings into account and, if yes, how? To that purpose, they can employ a bipolar reasoning style and a multipolar reasoning style. Although tort law is about determining the applicable rights and obligations between the plaintiff and defendant (bipolar reasoning), in light of the regulatory implications of tort law and developments in several tort systems, the relevance of considerations transcending this bipolar relationship (multipolar reasoning) is increasing. However, the possibilities for courts to engage in multipolar reasoning are restrained by the bipolar nature of tort law which gives rise to information and specialism deficits. This will be illustrated by referring to issues in relation to setting the standard of care and examining causation.